The Immune System of HIV-Exposed Uninfected Infants - Abu-Raya, Bahaa; Kollmann, Tobias R.; Marchant, Arnaud; MacGillivray, Duncan M. (Frontiers in Immunology, 2016)
Infants born to human immunodeficiency virus (HIV) infected women are HIV-exposed but the majority remains uninfected [i.e., HIV-exposed uninfected (HEU)]. HEU infants suffer greater morbidity and mortality from infections compared to HIV-unexposed (HU) peers. The reason(s) for these worse outcomes are uncertain, but could be related to an altered immune system state. This review comprehensively summarizes the current literature investigating the adaptive and innate immune system of HEU infants. HEU infants have altered cell-mediated immunity, including impaired T-cell maturation with documented hypo- as well as hyper-responsiveness to T-cell activation. And although prevaccination vaccine-specific antibody levels are often lower in HEU than HU, most HEU infants mount adequate humoral immune response following primary vaccination with diphtheria toxoid, haemophilus influenzae type b, whole cell pertussis, measles, hepatitis B, tetanus toxoid, and pneumococcal conjugate vaccines. However, HEU infants are often found to have lower absolute neutrophil counts as compared to HU infants. On the other hand, an increase of innate immune cytokine production and expression of co-stimulatory markers has been noted in HEU infants, but this increase appears to be restricted to the first few weeks of life. The immune system of HEU children beyond infancy remains largely unexplored.